2006
DOI: 10.1007/s11745-006-5082-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of margarine and butter consumption on distribution of trans‐18∶1 fatty acid isomers and conjugated linoleic acid in major serum lipid classes in lactating women

Abstract: Trans FA (TFA) have at least one trans double bond and comprise several isomers and types, including many of the CLA (e.g., c9,t11-18:2 CLA). Some TFA may have adverse effects (e.g., cardiovascular disease), whereas some are thought to have beneficial effects (e.g., anticarcinogenicity). The presence of TFA in human tissues and fluids is related to dietary intake, although this relationship is not completely understood--especially in regard to serum lipid fractions. This study was conducted as part of an inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…In the MIROS and CHUL cohorts, the 9t-18:1/11t-18:1 index was 0.67 and 0.39 respectively. Taken together, these results suggest that the pregnant women in the CHUL cohort had a diet richer in rTFA, and/or low in iTFA than the MIROS cohort [44]. Though, it would have been of interest to know the exact diet in TFA for the pregnant women of the two cohorts.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the MIROS and CHUL cohorts, the 9t-18:1/11t-18:1 index was 0.67 and 0.39 respectively. Taken together, these results suggest that the pregnant women in the CHUL cohort had a diet richer in rTFA, and/or low in iTFA than the MIROS cohort [44]. Though, it would have been of interest to know the exact diet in TFA for the pregnant women of the two cohorts.…”
Section: Discussionmentioning
confidence: 80%
“…This ratio is known to be reduced by high dairy fat intake [53]. A previous study in lactating women demonstrated the effect of a change in the diet on the fatty acid composition in different plasma lipid fractions [44]. Thus, when women increased their consumption of butter, the phospholipid 9t-18:1/11t-18:1 index indicated a ratio of 0.5.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results of Shahin et al. indicate that when CLA isomers are directly incorporated as dietary supplements, they preferentially accumulate in neutral lipids (Shahin, McGuire, Anderson, Williams, & McGuire, ). However, in our present study, elevated levels of RA were present also in tissues rich in polar lipids (phospholipids) which may be the result of high efficiency of PA conversion into RA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, comparison of data for total t FA is difficult since percentages of single fatty acids may vary according to the analysed plasma fractions (phospholipids vs . total lipids; [36]) and the applied method of analysis (GC-column, varying numbers of analysed/identified fatty acids, integration parameters, management of un-identified peaks).…”
Section: Discussionmentioning
confidence: 99%